Finance fictions : realism and psychosis in a time of economic crisis - De Boever, Arne (Fordham University Press, 2018)
Finance Fictions examines the tension between psychosis and realism in thecontemporary finance novel and shows that compared to earlier instances of thegenre (Wolfe; Ellis), the 21st-century finance novel (Alger; Harris;Houellebecq; Lerner) develops a new realist approach to a contemporary economyof financial instruments and automated trading.